Gambaran status gizi balita pada penggunaan garam beryodium di Desa Sangkan Gunung Kecamatan Sidemen, Kabupaten Karangasem - Thivyadharshini Uvaraju; G.N. Indraguna Pinatih (DiscoverSys Inc., 2017)
Nutritional status is one indicator of growth, nutritional status is a result of any use, absorption, and utilization of food. Iodine is needed in the body growth during gestation and early life, because iodine is an essential component in the formation of thyroid hormones. Thyroid hormone deficiency can reduce the activity of growth hormone such as (insulin growth hormone), which resulted in a number of developmental abnormalities and other functional. Toddlers (under five years) are one of age group in society most likely to suffer from nutritional disorders (susceptible nutrition) Methods: This study was a quantitative descriptive to describe the nutritional status of children in the use of iodized salt Sangkan Mountain Village district of Sidemen Karangasem regency. The target population was all Toddler Village Sangkan Mountains with a population of affordable homes that were accessible to researchers and have a toddler. This study used a total of 57 samples. Sample collection technique used is non-random consecutive sampling. Results: Nutritional Status based on Upper Arm Circumference (UAC), 5.3% Toddlers in the village Sangkan Gunung experiencing Malnutrition, and no toddlers (under 5 years old) were suffering Malnutrition. At 6 households using iodized salt, 5 infants (83%) with good nutrition and 1 infants (16.7%) with malnutrition. Meanwhile, from 51 families to use non-iodized salt, 49 infants (96.1%) with normal nutrition and 2 infants (3.9%) with malnutrition. Conclusion: The family of children who used iodized salt has the higher proportion of stunting than the family of children who did not use iodized salt.Â